2021
DOI: 10.3233/shti210148
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping COVID-19 Patients by Ventilation Therapy: Data Quality Challenges and Cohort Characterization

Abstract: The COVID-19 pandemic introduced unique challenges for treating acute respiratory failure patients and highlighted the need for reliable phenotyping of patients using retrospective electronic health record data. In this study, we applied a rule-based phenotyping algorithm to classify COVID-19 patients requiring ventilatory support. We analyzed patient outcomes of the different phenotypes based on type and sequence of ventilation therapy. Invasive mechanical ventilation, noninvasive positive pressure ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our study showed that the identification of COVID-19 cases (confirmed, probable, susceptible) can be challenging and time-consuming as it requires an extensive amount of manual review. The quality assurance of data and accurate use of standardized terminologies are important components for developing future phenotyping algorithms to identify COVID-19 cases with high performance for secondary-use research [ 51 ]. On an international level, lessons learned from the COVID-19 pandemic showed that there is a need to improve international research utilizing clinical data through connecting efforts from multiple countries to expand the capability of dealing with pandemic emergencies worldwide [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that the identification of COVID-19 cases (confirmed, probable, susceptible) can be challenging and time-consuming as it requires an extensive amount of manual review. The quality assurance of data and accurate use of standardized terminologies are important components for developing future phenotyping algorithms to identify COVID-19 cases with high performance for secondary-use research [ 51 ]. On an international level, lessons learned from the COVID-19 pandemic showed that there is a need to improve international research utilizing clinical data through connecting efforts from multiple countries to expand the capability of dealing with pandemic emergencies worldwide [ 21 ].…”
Section: Discussionmentioning
confidence: 99%